2022
DOI: 10.2147/prbm.s381976
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Trait Mindfulness on Subjective Well-Being of Kindergarten Teachers: The Sequential Mediating Roles of Emotional Intelligence and Work–Family Balance

Abstract: Teaching is a tough and stressful profession. Teachers' pressure and job burnout have become a common and serious problem, which makes teachers' subjective well-being feel a serious impact. The kindergarten environment is challenging and unique. The educational objects faced by kindergarten teachers are usually immature, which brings challenges to the teaching of kindergarten teachers. At the same time, in China, kindergarten teachers also need to undertake daily administrative management and other tasks. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 99 publications
0
5
0
1
Order By: Relevance
“…The scale is diffusely used in the research of Chinese population as subjects, and has been proved to be a good measurement tool by many studies. 47 The Cronbach’s α value of this scale was 0.961. The Cronbach’s α values of the subdimensions of the scale were 0.904, 0.888, 0.918, 0.877, and 0.902, respectively.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…The scale is diffusely used in the research of Chinese population as subjects, and has been proved to be a good measurement tool by many studies. 47 The Cronbach’s α value of this scale was 0.961. The Cronbach’s α values of the subdimensions of the scale were 0.904, 0.888, 0.918, 0.877, and 0.902, respectively.…”
Section: Methodsmentioning
confidence: 96%
“…The scale has nice applicability in Chinese research. 47 , 52 In order to make the scale better measure the happiness of the subjects in sports, we added expressions related to sports in the original scale items. One item is, “I am satisfied with my motor activity”.We performed a confirmatory factor analysis on the scale and the results showed that the model fit of the scale was perfect (ML x 2 = 7.336, df = 5, x 2 /df = 1.467, CFI = 0.997, TFI = 0.994, RMSEA = 0.031, SRMR = 0.014).…”
Section: Methodsmentioning
confidence: 99%
“… 84 At the same time, the scale is also widely used in the Chinese population. 85 A five-point Likert-type scale was used to assess how often each item was correct to respondents (1 = never or very rarely true and 5 = very often or always true). In this study, the Cronbach’s α value of the scale was 0.959, and the Cronbach’s α value of the sub-dimension scales were 0.933, 0.910, 0.939, 0.895, and 0.927, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Respondents identified that being mindful could impact overall subjective well-being. Pan et al (2022) found mindfulness to predict subjective well-being. They also found that the two variables are mediated by emotional intelligence and work-family balance.…”
Section: Literature Reviewmentioning
confidence: 98%